(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Eimeria (coccidiosis) is a common internal parasitic disease in poultry, the main infectious agents of which are protozoa of the genus Eimeria. This article analyzes the biology, structure and development cycle of oocysts in eimeria in poultry. Oocysts play a central role in the spread of the disease and its transmission among poultry. How they survive in the external environment, the process of sporulation and their role as an infectious stage are considered in detail. The article also highlights the importance of oocysts in disease prevention. The results of the study provide a scientific basis for effective control and prevention measures for eimeria in poultry.